1999
DOI: 10.1042/bj3410713
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of an intracellular protein complex that binds fibroblast growth factor-2 in bovine brain

Abstract: The fibroblast growth factor (FGF) family is composed of polypeptides with sequence identity which signal through transmembrane tyrosine kinase receptors. We report here the purification from bovine brain microsomes of an FGF-2-binding complex composed of three proteins of apparent molecular masses 150 kDa, 79 kDa and 46 kDa. Only the 150 kDa and 79 kDa proteins bound FGF-2 in cross-linking and ligandblotting experiments. Binding of FGF-2 to p79 is enhanced in the presence of calcium. Peptide sequences allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…However, sequence comparisons have revealed that the 78 kDa gastrin‐binding protein (or gastrin/CCK‐C receptor) is closely related to a family of mitochondrial proteins involved in fatty acid oxidation 17 . The question of how a mitochondrial protein may appear at the cell surface has been answered by a recent report that two mRNA, differing only in the signal sequence they encode, exist for the 78 kDa gastrin‐binding protein 34 . One signal sequence targets the protein to the endoplasmic reticulum, and hence presumably to the cell surface, while the other targets the protein to the mitochondria 34 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, sequence comparisons have revealed that the 78 kDa gastrin‐binding protein (or gastrin/CCK‐C receptor) is closely related to a family of mitochondrial proteins involved in fatty acid oxidation 17 . The question of how a mitochondrial protein may appear at the cell surface has been answered by a recent report that two mRNA, differing only in the signal sequence they encode, exist for the 78 kDa gastrin‐binding protein 34 . One signal sequence targets the protein to the endoplasmic reticulum, and hence presumably to the cell surface, while the other targets the protein to the mitochondria 34 …”
Section: Discussionmentioning
confidence: 99%
“…17 The question of how a mitochondrial protein may appear at the cell surface has been answered by a recent report that two mRNA, differing only in the signal sequence they encode, exist for the 78 kDa gastrin-binding protein. 34 One signal sequence targets the protein to the endoplasmic reticulum, and hence presumably to the cell surface, while the other targets the protein to the mitochondria. 34 The receptor binding data presented herein have significant implications for our understanding of the mechanism by which gastrin 17 gly stimulates growth of the colonic mucosa.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations